Effect of modified phosphogypsum on the dimensional stability of supersulfated cement-based materials - Qingqing Jin; Lu Wang; Zhisheng Ren; Xinyu Li; Shuhua Liu (Case Studies in Construction Materials)
Compared to ordinary Portland cement (OPC), supersulfated cement (SSC) is an environmentally friendly cement. Phosphogypsum (PG) is commonly utilized as a sulfate activator in SSC. In this study, the effect of modified PG on the dimensional stability of supersulfated cement-based materials (SSCM) was investigated. Taking the point of decrease in internal relative humidity as the time-zero of autogenous shrinkage, the lime neutralized PG (NPG) reduced the autogenous shrinkage of SSCM by 15.03 % at 28 days and 16.26 % at 90 days, suppressing the development of autogenous shrinkage in SSCM. However, the calcined PG (CPG) displayed the opposite trend. Both modified PG improved the drying shrinkage of SSCM, and the NPG resulted in less water loss. Compared to OPC, SSCM exhibited a rapid increase in autogenous shrinkage relative to drying shrinkage, which was intensified with CPG. Obviously, the NPG demonstrated superior modification effects on the dimensional stability of SSCM compared to CPG.